The Effect of Space Environments on the Material Degradations: The Current Understanding and Proposed Synergistic Effects - Pornpibunsompob, Tosapolporn; Saidarasamoot, Sittha (Science Essence Journal, 2024)
The objective of this research was to study the effect of micrometeoroids (MM) and space debris (SD), atomic oxygen (AO) and vacuum on space material degradation. The synergistic effect was also proposed inferences based on the comprehensive findings of prior researches. The research was carried out in four steps including article review design, conducting review, collecting and analyzing information and article structuring and writing. The results showed that MM and SD impacted on somewhere of spacecraft, leading to delamination, crack, or fracture. Outgassing is a key degradation existing in vacuum environments, especially on polymeric-based materials. Polyetheretherketone (PEEK) performed the lowest outgassing rate comparative to Polybenzimidazole (PBI) and Polyimide (PI). AO generates from dissociation of oxygen gas in low earth orbit (LEO). Thermal AO broke apart the covalent bonds and formed volatile products. Additionally, AO reacted to some metals, causing several kinds of metal oxides. The second effect was erosion caused by hyperthermal AO. Erosion yields of polymers were higher than metals because of mechanical and chemical properties differentiation. The synergistic effect among two environmental conditions would further contribute to the degradation of space materials. In this review article, the mutual effect of MM and SD, outgassing and AO was proposed. MM and SD would impact on space material and originate the delamination and/or abrasion on the surface. Hyperthermal AO would erode and reveal material’s surface and then, enlarge the damaged surface area. Thermal AO accelerated oxidation reaction and volatile products. Moreover, vacuum would enhance outgassing and release many types of gases. The proposed mechanism should be validated in the future.